1993
DOI: 10.1021/ed070p656
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry tours for high school students: Connecting chemistry and business

Abstract: Efforts to show high school students the relevance of chemistry in their lives are more powerful when students go on field trips to visit businesses that are related to chemistry. The author describes such a trip, where students visited the Dept. of Justice Criminalistics Lab at a local university.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…3 This is not to suggest that field trips should entirely replace traditional laboratories that allow students to draw conclusions from laboratory data and gain an understanding of the scientific method. It was found that the majority of students felt that field trips were better educational experiences than were traditional laboratory exercises and recommended that the field trip portion of the class should be expanded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 This is not to suggest that field trips should entirely replace traditional laboratories that allow students to draw conclusions from laboratory data and gain an understanding of the scientific method. It was found that the majority of students felt that field trips were better educational experiences than were traditional laboratory exercises and recommended that the field trip portion of the class should be expanded.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the majority of students felt that field trips were better educational experiences than were traditional laboratory exercises and recommended that the field trip portion of the class should be expanded. 3 This is not to suggest that field trips should entirely replace traditional laboratories that allow students to draw conclusions from laboratory data and gain an understanding of the scientific method. Field trips can however complement traditional laboratory experiments by providing real-world learning situations that help put chemistry in context for non-science majors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that secondary science instruction is most effective when it is made relevant to the lives of the students (8). This requires that teachers remain current on chemical discoveries and applications that have an impact on everyday life.…”
mentioning
confidence: 99%